Effects of genital ulcer disease and herpes simplex virus type 2 on the efficacy of male circumcision for HIV prevention: Analyses from the Rakai trials. - Ronald H Gray; David Serwadda; Aaron A R Tobian; Michael Z Chen; Frederick Makumbi; Tara Suntoke; Godfrey Kigozi; Fred Nalugoda; Boaz Iga; Thomas C Quinn; Lawrence H Moulton; Oliver Laeyendecker; et al. (PLoS Medicine)
Background Randomized trials show that male circumcision (MC) reduces the incidence of HIV and herpes simplex virus type 2 (HSV-2) infections, and symptomatic genital ulcer disease (GUD). We assessed the role of GUD and HSV-2 in the protection against HIV afforded by MC. Methods and findings HIV-uninfected men were randomized to immediate (n = 2,756) or delayed MC (n = 2,775) in two randomized trials in Rakai, Uganda. GUD symptoms, HSV-2 status, and HIV acquisition were determined at enrollment and at 6, 12, and 24 mo of follow up. Ulcer etiology was assessed by PCR. We estimated the prevalence and prevalence risk ratios (PRRs) of GUD in circumcised versus uncircumcised men and assessed the effects of HSV-2 serostatus as a risk-modifying factor for GUD. We estimated the proportion of the effect of MC on HIV acquisition that was mediated by symptomatic GUD, and by HSV-2 infection. Circumcision significantly reduced symptomatic GUD in HSV-2-seronegative men (PRR = 0.51, 95% [confidence interval] CI 0.43-0.74), HSV-2-seropositive men (PRR = 0.66, 95% CI 0.51-0.69), and in HSV-2 seroconverters (PRR = 0.48, 95% CI 0.30-0.79). The proportion of acute ulcers due to HSV-2 detected by PCR was 48.0% in circumcised men and 39.3% in uncircumcised men (chi(2)p = 0.62). Circumcision reduced the risk of HIV acquisition in HSV-2 seronegative men (incidence rate ratio [IRR] = 0.34, 95% CI 0.15-0.81), and potentially in HSV-2 seroconverters (IRR = 0.56, 95% CI 0.19-1.57; not significant), but not in men with prevalent HSV-2 at enrollment (IRR = 0.89, 95% CI 0.49-1.60). The proportion of reduced HIV acquisition in circumcised men mediated by reductions in symptomatic GUD was 11.2% (95% CI 5.0-38.0), and the proportion mediated by reduced HSV-2 incidence was 8.6% (95% CI -1.2 to 77.1). Conclusions Circumcision reduced GUD irrespective of HSV-2 status, but this reduction played only a modest role in the protective effect of circumcision on HIV acquisition.